An Analysis of Global Marketing Strategy for the Malaysian Wooden Furniture Industry - Yeap, Teik Bu (1999)

(untitled)
The wooden furniture industry has shown a remarkable achievement over the last decade, especially its export performances. This industry like other natural evolving clusters is characterised by small-and-medium-scale industries (SMIs), labour intensive and less specialise production technology. The turning point of the industry began with the launching of the first Industrial Master Plan (1986-1995) (IMP), whereby the government provided consistent and user-friendly policy measures to allow healthy competition among the manufacturers and entrepreneurship development. The influx of foreign investments spurred the technology transfer process in the furniture industry by introducing the private subcontracting system which is a global marketing strategy especially the Original Equipment Manufacturing (OEM), to local entrepreneurs. The resource advantage and cheap unskilled labour allowed local entrepreneurs to have sufficient time to nurture and to penetrate new markets.New opportunities and threats to the industry were unveiled when the Second Industrial Master Plan underwent a revision in its objectives owing to the changes of the internal and external factors of the industry. Malaysia has already placed a firm economic foundation by establishing intra- and inter-linkages, which to a certain extent provides better opportunities to adopt other global marketing strategies. These strategies may even ensure a more sustainable growth to the industry and is able to reap a price premium. On the other hand, the Malaysian wooden furniture industry needs to deal with more uncertainties as its close rivals; Thailand, Indonesia and China, as well as other emerging economies such as Latin America, and East European countries, acquire similar marketing strategy. The formation of the regional groupings such as the European Union and North American Free Trade Agreement provide more uncertainties in the world economy. The objectives of the study are derived from feedbacks of the manufacturers' point of view and the issues they put forwarded: a) to analyse factors contributing to their global marketing strategy; and b) to examine the factors leading to different global marketing strategies adopted in the wooden furniture industry. A comprehensive literature review highlighting a firm's decision maker in exporting, the choice of competition on global marketing strategies, value chain concept, as well as the Industrial Master Plan (1996-2005) have assisted the formulation of the hypotheses. Hypothesis One proposes that the firm's decision on a global marketing strategy for wooden furniture industry is influenced by the external and internal factors. The external factors include the government's domestic incentives and the risk factors. The internal factors are the competitiveness of the domestic and foreign rivals, the decision maker's previous experiences and decision maker's attitude or expectation towards exporting. Meanwhile, Hypothesis Two suggests that size of the firm's, the firm's experiences in exporting, the decision maker's attitude, current global marketing strategy and the firms establishment can affect the firm's choice in global marketing strategy. Through factors analysis, the findings confirm the government's primary incentives, political environment risk factor, business risk factors, pioneer status, firm's competitiveness over domestic rivals, firm' s competitiveness over foreign rivals and the decision maker's expectation of exporting are the key factors explaining 79.7 percent of the hypothesis. Firm's characteristics and the decision maker's attitude towards exports are significant to Hypothesis Two. The findings draw the attention to the manufacturers as well as the policy makers that customers value and Porter's five-competitive forces of entries model are important factors to consider in formulating both a business strategy and the government policies. The policies that will bring about a strategy shift include research and development, human resources development (HRD), marketing and information gathering, infrastructure, financial assistant and raw material procurement.